Investigation of mastitis-related culling in a dairy farm in south Great Hungarian Plain - Tóth, Violetta; Nagypál, Virág; Gulyás, László; Mikó, Edit (Animal welfare, Ethology and Housing Systems (AWETH), 2020)
Most dairy farms apply the most up to date and modern feeding, keeping, milking, and animal health technologies in order to achieve cost efficient production. However, besides extremely high milk production, farmers face many other problems. Useful life is generally shortened and early culling of cows is a common problem too. In 2018, the average annual lactation was 2.1 in a Hungarian Holstein-Friesian herd. The most important goal is to keep cattle with high-yielding in production as long as possible. Thus useful life can be increased. There are two types of culling. One is strategically managed culling and the other is forced culling. Based on the data of 5 years from the examined dairy cattle farm, main reasons of culling and lactation with highest culling rate were determined. The number of diseases in different lactations was revealed as well. 30% of the culling was caused due to udder health reasons and 22% due to reproductive disorders. The overall rate of culling was caused by inadequate production, lameness and metabolic diseases was 12%. Other diseases and managerial decisions resulted in a total of 35% culling. The culling rate per lactations was: 23% in lactation 1th, 32% in lactation 2nd, 25% in lactation 3th, 12% in 4th lactation, 8% in 4< lactations. During the first lactation, the causes of culling were: reproductive disorders 7.74%, udder health 4.94% and inadequate production 4.5%.